REVITALISASI KAMPUNG WISATA SOHEDEN (SOCO HERBAL GARDEN) KABUPATEN MAGETAN - Fatmala, Fenti; Sari, Nika Kartika; Yusdita, Elana Era (Jurnal Terapan Abdimas, 2024)
Abstract. The purpose of this article is to explain the implementation of community service carried out by the Ormawa Himadik PPK team. The program was implemented in Soco Village, Bendo District, Magetan Regency with the theme Eduwisata. Soco Village is one of the villages that has started implementing the Edutourism Village program since 2021. However, everything seems neglected and not well maintained due to the lack of visitors and the absence of good and correct tourism management. The activity implementation method consists of 12 methods ranging from surveys to making reports. The results of this program are new conditions including (1) Tourism managers gain knowledge of soft skills and hard skills for tourism management and financial management; (2) After the formation of the POKDARWIS management structure, it is hoped that there will be a clear division of tasks based on the knowledge presented previously; (3) The existence of supporting facilities and infrastructure for the safety and comfort of visitors, namely plant name labels, increasing the number of plant species, repairing miniature ship ladders, and learning facilities for Pancasila student profiles; (4) Arrangement of tourist routes and installation of tourist layouts in Soco Village; (5) There are additional visitors after the facilities and infrastructure have increased, both from students and the general public Abstrak. Tujuan dari artikel ini adalah untuk menjelaskan implementasi dari pengabdian masyarakat yang dilaksanakan tim PPK Ormawa Himadiksi. Program dilaksanakan di Desa Soco, Kecamatan Bendo, Kabupaten Magetan dengan tema Eduwisata. Desa Soco merupakan salah satu desa yang mulai melaksanakan program Desa Eduwisata sejak tahun 2021. Akan tetapi semua terkesan terbengkalai dan tidak terawat dengan baik karena sepinya pengunjung serta tidak adanya pengelolaan wisata yang baik dan benar. Metode pelaksanaan kegiatan terdiri dari 12 metode mulai dari survey sampai dengan pembuatan laporan. Hasil dari program ini adanya kondisi baru meliputi (1) Pengelola wisata mendapatkan ilmu softskill dan hardskill untuk pengelolaan wisata dan manajemen keuangan; (2) Setelah terbentuknya struktur kepengurusan POKDARWIS diharapkan ada pembagian tugas yang jelas berdasarkan ilmu yang disampaikan sebelumnya; (3) Adanya sarana dan prasarana penunjang untuk keselamatan dan kenyamanan pengunjung, yaitu label nama tanaman, penambahan jumlah spesies tanaman, perbaikan tangga miniatur kapal, dan sarana pembelajaran profil pelajar pancasila; (4) Adanya penataan alur wisata dan pemasangan layout wisata di Desa Soco; (5) Adanya penambahan pengunjung setelah sarana dan prasarana bertambah baik dari kalangan pelajar maupun umum